Fatal intra-alveolar pulmonary bleeding complicating pulmonary embolectomy. Issue 4 (July 1971) - Makey, A. R.; Bliss, B. P.; Ikram, H.; Sutcliffe, M. M. L.; Emery, E. R. J.
Abstract : Two patients are reported in whom fatal alveolar pulmonary haemorrhage occurred after pulmonary embolectomy. Possible causes and methods of prevention are discussed.